SIRT3 regulates cancer cell proliferation through deacetylation of PYCR1 in proline metabolism - Chen, Shuaiyi; Yang, Xin; Yu, Miao; Wang, Zhe; Liu, Boya; Liu, Minghui; Liu, Lu; Ren, Mengmeng; Qi, Hao; Zou, Junhua; Vucenik, Ivana; Zhu, Wei-Guo; et al. (Neoplasia (New York, N.Y.), 2019)
SIRT3 is a major mitochondrial deacetylase, which regulates various metabolic pathways by deacetylation; however, the effect of SIRT3 on proline metabolism is not reported. Pyrroline-5-carboxylate reductase 1 (PYCR1) participates in proline synthesis process by catalyzing the reduction of P5C to proline with concomitant generation of NAD+ and NADP+. PYCR1 is highly expressed in various cancers, and it can promote the growth of tumor cells. Here, through immunoprecipitation and mass spectrometry, we found that PYCR1 is in SIRT3’s interacting network. PYCR1 directly binds to SIRT3 both in vivo and in vitro. CBP is the acetyltransferase for PYCR1, whereas SIRT3 deacetylates PYCR1. We further identified that K228 is the major acetylation site for PYCR1. Acetylation of PYCR1 at K228 reduced its enzymatic activity by impairing the formation of the decamer of PYCR1. As a result, acetylation of PYCR1 at K228 inhibits cell proliferation, while deacetylation of PYCR1 mediated by SIRT3 increases PYCR1’s activity. Our findings on the regulation of PYCR1 linked proline metabolism with SIRT3, CBP and cell growth, thus providing a potential approach for cancer therapy.